THE ACCOUNTANT AS AN ARTIST. - McCowen, George B. (The Accounting Review, 1946)
Accounting is not a science; it is an art. The general ledger of an accounting system is a picture of a business enterprise in action, but it is not a photographic picture. Rather it is cubistic or surrealistic, and therefore symbolical in nature. It visualizes, for the management and others, one link in the chain of economic activity whereby man makes his living. Put all accounting systems together in a chain, and the totality of economic effort would spread like a mighty mural before our eyes. There sometimes is a look about the eyes of accountants that has mistakenly been compared with the cold stare of a fish. It does not come from eye strain from unemotionally looking too hard at figures. Instead, it comes from mentally seeing far-off places and far-off activities. For accountants look with an inner eye at commerce and industry-a scene which is one of the mightiest and most complex to be viewed by man. The accountant can glimpse the whole panorama. The pen, the ledger the ink are his artist's brush, canvas, and paint with them he captures some phases of each dramatic movement of the scene.